Visualization of mouse induced pluripotent stem cells for evaluation of tracheal regeneration. (April 2015) - Yoshie, Susumu; Ikeda, Masakazu; Imaizumi, Mitsuyoshi; Otsuki, Koshi; Nomoto, Yukio; Wada, Ikuo; Omori, Koichi
Abstract: Conclusion: Visualization of mouse induced pluripotent stem (iPS) cells with the use of a fluorescent protein was successfully achieved for evaluation of tracheal regeneration. Objectives: Tracheal epithelial cells derived from iPS cells are expected to be a useful cell source for tracheal regeneration. Our previous study demonstrated that mouse iPS cells differentiated into tracheal epithelial cells. However, when they are implanted into tracheal defects in experimental animals, it is difficult to determine whether the regenerated tracheal epithelium is in fact derived from iPS cells. The purpose of this study was to develop a visualization technique for iPS cells for evaluation of tracheal regeneration. Methods: Fluorescent marker tdTomato was transfected into iPS cells. Tracheal epithelial cells were generated from tdTomato-labeled iPS cells using embryoid body formation to detect the expression of tdTomato. The artificial material with tdTomato-labeled iPS cells was implanted into tracheal defects in nude rats. The survival and distribution of tdTomato-labeled iPS cell-derived cells were examined using the IVIS Imaging System and immunostaining. Results: The expression of tdTomato was detected in both undifferentiated cells and tracheal epithelial cells in vitro. tdTomato-labeled iPS cell-derived cells were successfully detected in the tracheal defects by IVIS Imaging System and immunostaining.